Prevalence of left bundle branch block and CRT treatment in a large regional unselected ECG database. (14th October 2021) - Lind, S; Gatti, P; Kristjansdottir, I; Gadler, F
Abstract: Introduction: Heart failure is a clinical syndrome in which signs and symptoms are due to functional and/or structural abnormalities of the heart which prevent the necessary supply of oxygenated blood or do so at the expense of high filling pressures. It has a prevalence of 1–2% in the western world and increasing prevalence with increasing age. While the prognosis for coronary heart disease has improved significantly, the same does not apply for heart failure, perhaps because some effective treatment methods have not been sufficiently implemented in health care. One effective but underutilized heart failure treatment is the cardiac resynchronisation therapy (CRT), that coordinates the contraction of the left and right ventricles via a pacemaker (PM). CRT treatment is an evidence based treatment recommended by among other the ESC guidelines for heart failure. Clinical studies have suggested decreases in mortality, hospitalization, morbidity and improvements in quality of life for heart failure patients receiving a CRT. Purpose: To find a new clinical pathway to improve CRT implementation and to evaluate if it might be optimized through ECG-based surveillance and thus improving prognosis. Methods: In a population of approximately 2.5 million people in our region we investigated the University Hospital's ECG database between 2000 and 2018. During which time 432 108 adult patients with 1 482 489 ECG's presented to the hospital. We searched and found 5 511 unique patients with the following ECG criteria: QRS ≥150 ms at any time, LBBB and Non pace. According to the Pacemaker Registry we excluded 771 patients that had previously received a PM/CRT. We also identified patients with diagnosis of heart failure by using the ICD-10 codes (I42.0 and I50). Results: Our final cohort consists of 4 740 patients. The median age was 75 (19–112) years, 34.5% were female and 14.9% were subsequently implanted with a CRT (60% with CRT-D). The median time to CRT implantation from the first ECG with LBBB was 244 (IQR 994) days. Of the 4 740 patients 20.6% had a previous hospitalistion for heart failure with a median delay from the hospitalisation to CRT implantation of 5 (IQR 5.4) years. Conclusions: Our observational data from a large real-life regional ECG database show there is a considerable number of heart failure patients that could benefit from CRT treatment. Using an existing ECG database could be useful in finding patients with indication for CRT implantation. This could possibly influence morbidity and mortality in a regional heart failure population by minimizing the delay of CRT treatment. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Karolinska University Hospital Research Fund